دور الإصلاحات الاقتصادية في تحسين المناخ الاستثماري دراسة حالة الجزائر 2000 ــ 2016 - شنوف, عبد الرؤوف (university of eloued, 2018)
حاولنا في هذه الدراسة إبراز أهمية الإصلاحات الاقتصادية في تجاوز الأزمات التي تمر بها الدولودورها الفعال في تحسين الأداء الاقتصادي للدولة، وتناولنا ببعض التفصيل الإصلاحات التي قامت بها الجزائر خلال الفترة الممتدة من 2000 إلى 2016وأكدنا على ضرورة الاستمرار في هذه المسيرة مع التقويم المستمر لها حتى تؤدي أهدافها المرجوة منها. كما حاولنا التأكيد على أهمية هذه الإصلاحات ومساهمتها الفعالة في تحسين المناخ الاستثماري وبالتالي في جذب الاستثمارات الأجنبية المباشرة،وبالنسبة للجزائر نجد التحسن النسبي في مناخ استثمارها مع ملاحظة بقائها في مراتب متأخرة نسبيا ضمن تقارير مناخ الاستثمار وسهولة ممارسة الأعمال ما يتطلب منها المسارعة في إجراء إصلاحات متخصصة قصد استهداف المستثمرين الأجانب ومحاولة استقطابهم إلى الجزائر. بخصوص الاستثمارات الأجنبية المباشرة الواردة إلى الجزائر لاحظنا تحسنها خلال الفترة،وتبقى إمكانيات الجزائر تؤهلها لاستقطاب استثمارات أكثر. We tried in this study to highlight the importance of economic reforms in overcoming the crises experienced by countries and their effective role in improving the economic performance of the state. We discussed in some detail the reforms undertaken by Algeria during the period from 2000 to 2016, We confirmed the need to continue this process with continuous evaluation until to achieve their desired objectives. We also tried toconfirm the importance of these reforms and their effective contribution to the improvement of the investment climate and thus attract foreign direct investments. For Algeria, the relative improvement in its investment climate is observed, with its relatively low levels of investment climate reports and ease of doing business. Targeting foreign investors and trying to attract them to Algeria. With regard to foreign direct investment received in Algeria, we noticed an improvement during the period studied, and the possibilities of Algeria continue to qualify for attracting more investments.
مذكرة ماستر تجارة دولية
Keywords: إصلاح اقتصادي، مناخ الاستثمار، استثمار أجنبي مباشر.